2019
DOI: 10.1002/mgg3.792
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive immune repertoire study for patients with pulmonary tuberculosis

Abstract: Background Tuberculosis (TB) is a major global health problem and has replaced HIV as the leading cause of death from a single infectious agent. Methods Here, we applied high throughput sequencing to study the immune repertoire of nine pulmonary tuberculosis patients and nine healthy control samples. Results Tuberculosis patients and healthy controls displayed significantly different high express clones and distinguishable sharing of CDR3 seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Remarkably, by sequencing, we revealed that notable disease-severity-associated clones, disease-preferred V β , J β , and V-J junctions exist in OSA and diversity and new clonotypes dramatically increased, suggesting unusual T cell activation and memory for a series of unique MHC-peptides complex exposure. By contrast, a significant decrease in diversity is a common phenomenon that can be found in most previous studies on other conditions, such as cancer, tuberculosis ( Fu et al., 2019 ), pneumonia of COVID-19 ( Chang et al., 2021 ), acute myocardial infarction ( Zhong et al., 2019 ), and subarachnoid hemorrhage ( Kim et al., 2020 ) and corresponds with activation of specific associate TCR clusters to emergent stimuli. Notably, there are several significant factors that can affect the TCR repertoire diversity: (1) aging: the thymus begins to wither after puberty, gradually losing naïve T lymphocytes production, decreasing the ability to respond to neoantigens with age ( Douek et al., 1998 ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Remarkably, by sequencing, we revealed that notable disease-severity-associated clones, disease-preferred V β , J β , and V-J junctions exist in OSA and diversity and new clonotypes dramatically increased, suggesting unusual T cell activation and memory for a series of unique MHC-peptides complex exposure. By contrast, a significant decrease in diversity is a common phenomenon that can be found in most previous studies on other conditions, such as cancer, tuberculosis ( Fu et al., 2019 ), pneumonia of COVID-19 ( Chang et al., 2021 ), acute myocardial infarction ( Zhong et al., 2019 ), and subarachnoid hemorrhage ( Kim et al., 2020 ) and corresponds with activation of specific associate TCR clusters to emergent stimuli. Notably, there are several significant factors that can affect the TCR repertoire diversity: (1) aging: the thymus begins to wither after puberty, gradually losing naïve T lymphocytes production, decreasing the ability to respond to neoantigens with age ( Douek et al., 1998 ).…”
Section: Discussionmentioning
confidence: 72%
“…Thus, there was no reliable method for diagnosing and evaluating OSA from peripheral blood before our study. As a novel approach to identifying biomarkers, TCR immune repertoires were previously proved efficient in identifying infectious diseases, autoimmune diseases, carcinoma, and even acute myocardial infarction ( Fu et al., 2019 ; Chang et al., 2021 ; Zhong et al., 2019 ; Kim et al., 2020 ). The complex but unique chronic inflammatory features of OSA, including CIH-induced cell injury and apoptosis products, endothelial function impairment, abnormal metabolomics, colonized microbial flora changes, the impacts of sleep fragmentation, and even early lesion in the cardiovascular system ( Lavie, 2015 ; Khalyfa, Kheirandish-Gozal & Gozal, 2018 ; Humer, Pieh & Brandmayr, 2020 ), can probably contribute to forming a disease-specific repertoire landscape.…”
Section: Discussionmentioning
confidence: 99%
“…S1-S3). The lowest tertile of TCR surface protein expression (n = 6) was noted to have <0.5% surface TCR protein expression of circulating CD3 + cells, the threshold previously established as a highly expanded clone (10,11). These 6 patients were designated as an "expression-low" cohort for further analyses, whereas the remaining 10 patients were designated as "expression-high."…”
Section: Transgenic Tcr-engineered T Cells Display Strong Persistence...mentioning
confidence: 99%
“…Significant progress has been made in methods of analyzing aspects of the immune repertoire, providing measures of clonality, diversity, VDJ gene usage, sequence motifs, and network characteristics ( 5 ). These methods, in turn, have led to discoveries of repertoire characteristics in normal aging ( 6 , 7 ), and in diseases such as cancer ( 8 , 9 ), autoimmune disorders ( 9 , 10 ), and infections ( 11 , 12 ). Existing methods have focused on separate analyses of BCR and TCR repertoires, however, and no study to date has attempted to discover existing parallels within an individual’s BCR and TCR repertoires.…”
Section: Introductionmentioning
confidence: 99%